APPLICATION OF THE ROLLING PERIOD FORMULA IN DETERMINING METACENTRIC HEIGHT (GM) FOR SHIP STABILITY A CASE STUDY OF THE TRAINING SHIP SULTAN HASANUDDIN - Sulistiana, Oktavera; Bokau, Joe Ronald Kurniawan; Djajasasana, Egbert Edward; Umatjina, Firdaus (International Journal of Social Service and Research, 2025)
The Sultan Hasanuddin Training Ship of PIP Makassar was selected as the research object for this study. The study aims to analyze the stability of the ship by focusing on calculating the metacentric height (GM) value based on the moment of static stability, incorporating both manual methods and computer applications that generate GM values as indicators of seaworthiness according to the Intact Stability Code. The research method used in this study is a case study that involves descriptive, numerical, and comparative analysis of various ship parameters, including the length, width, and inside the ship, as well as other measurements required in the stability calculation. The GM calculation is carried out using the static stability moment approach and compared with the results of recording the ship's rolling period. The results show that the GM value generated from the calculation of the existing static stability moments, if deducted from the total value of the Virtual Loss of GM due to the inertia moment in the slack tanks, will produce an effective GM worth that is used as the basis for the ship stability benchmark. This research could contribute significantly to improving safety protocols and design standards in maritime operations. The benefits of this research include providing theoretical information for lecturers and cadets of PIP and commercial shipping officers, enriching teaching materials on ship construction and stability, and promoting a safety culture by offering practical information to estimate ship stability conditions before more detailed calculations are made.